Exploring the Use of State Medical Cannabis Legislation as a Proxy for Medical Cannabis Use Among Patients Receiving Chemotherapy - Gressler, Laura E.; Baltz, Alan P.; Costantino, Ryan C.; Slejko, Julia F.; Onukwugha, Eberechukwu (Current treatment options in oncology, 2021)
Opinion statement The use of medical cannabis is expanding in the USA. Due to conflicting, low-quality evidence, many oncologists may not feel confident to recommend it to patients. Given the potential for legal and financial risks when conducting clinical trials with medical cannabis, the use of observational data should be explored. Observational data that directly capture medical cannabis use in relation to prescription medications and track the prevalence and patterns of cannabis use is sparse. To gain insights into the role medical cannabis plays in the pharmaceutical landscape, proxies such as cannabis legislation need to be explored. In the context of recommendation-nonadherent antiemetic prescribing among patients experiencing chemotherapy-induced nausea and vomiting, medical cannabis may be a suitable alternative to an antiemetic in states that allow medical cannabis. Findings suggest that legislation may impact the use of certain antiemetics in states with cannabis legislation in place. The presence or absence of legislation regarding medical cannabis use may serve as an early, observable surrogate marker of medical cannabis use in the community. In light of the paucity of clinical trials and observational datasets that capture cannabis use, there remains a tremendous need for the development of methodologies or standardized datasets that appropriately and reliably capture the use of medical cannabis to facilitate research into its clinical application and effect on prescription medication use. Standardizing the reporting and destigmatizing use could eliminate the dependence upon proxy measures as a substitute for more extensive data and go a long way in improving data capture, thus allowing us to generate knowledge and hypotheses from observational data until research conditions improve and allow for expanded clinical trials involving medical cannabis.